Competition in the post-trade markets: A network economic analysis of the securities business - Günter Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2004)
In order to analyse the role of competition in the post-trade markets a normative network economic analysis of securities business is provided. The theory of monopolistic bottlenecks constitutes the theoretical reference point for this analysis in order to identify stable network specific market power. It is shown that clearing and settlement are competitive value-added telecommunications services and therefore do not justify ex ante market power regulation. Precondition for competition on the markets for clearing and settlement is non-discriminatory access to the complementary technical regulatory function – the notary function (authenticity, registry, links between competing end custodians).
Keywords: 330; Wertpapierhandel; Wertpapiergeschäft; Verrechnungsverkehr; Wettbewerb; Mehrwertdienst; Netzzugang; Bottleneck; Monopol